2011
DOI: 10.1590/s0102-695x2011005000114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antiproliferative activity of essential oil from aerial parts of a medicinal herb Artemisia herba-alba

Abstract: Artemisia herba-alba Asso., Asteraceae, is widely used in Morrocan folk medicine for the treatment of different health disorders. However, no scientific or medical studies were carried out to assess the cytotoxicity of A. herba-alba essential oil against cancer cell lines. In this study, eighteen volatile compounds were identified by GC-MS analysis of the essential oil obtained from the plant's aerial parts. The main volatile constituent in A. herba-alba was found to be a monoterpene, Verbenol, contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…Similarly, Dahmani-Hamzaoui and Baaliouamer [39] identified the davanon in the essential oil of sagebrush Djelfa. Tilaoui et al [40] showed that the oil sagebrush of Imilchil ErRachidia (Morocco) contains the verbenol as major compound. The eucalyptol is identified as the major constituent in the essential sagebrush oil from southern Spain (41% maximum) [37] and Egypt [41].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Dahmani-Hamzaoui and Baaliouamer [39] identified the davanon in the essential oil of sagebrush Djelfa. Tilaoui et al [40] showed that the oil sagebrush of Imilchil ErRachidia (Morocco) contains the verbenol as major compound. The eucalyptol is identified as the major constituent in the essential sagebrush oil from southern Spain (41% maximum) [37] and Egypt [41].…”
Section: Resultsmentioning
confidence: 99%
“…Essential oils of A. absinthium which contained higher amounts of trans-sabinyl acetate and cis/trans-thujones exhibited more toxicity on brine shrimp (Judzentiene et al, 2012). Moreover, the essential oils of A. capillaris and A. herbaalba are regarded as good candidates for further study, because they showed significant anti-proliferative activity against the human oral cancer and acute lymphoblastic leukaemia (CEM) cell lines respectively (Cha et al, 2009;Tilaoui et al, 2011). Dichloromethane extracts of A. annua exhibited higher cytotoxicity in comparison with methanol extracts against HeLa cancer cells (Efferth et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in Artemisia species, artemisinin is not the unique medicinal molecule. The genus is abundant with other sesquiterpene lactones (de Almeida et al, ; Ivanescu, Miron, & Corciova, ; Shoaib et al, ; Tilaoui et al, ), which could have antihelmintic effects with less mammalian toxicity risk (Kerboeuf, Riou, & Guégnard, ).…”
Section: Pharmacological Properties Of Artemisininmentioning
confidence: 99%